Revenue management and air cargo - Morello, Gina (Henry Stewart Talks, 2009)
Requirements for revenue management, Applications of revenue management in cargo, Fundamental cargo issues, Capacity forecasting, Market segmentation, Demand forecasting, Optimization models, Revenue management execution, Advanced topics in cargo revenue management